Perancangan dan Implementasi Video Media Pembelajaran Produk Kreatif Dan Kewirausahaan di SMKN 2 Batam Menggunakan MDLC - Madani umpu nikan; Diny Anggriani Adnas (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The development of the industry that is not in sync with the provision of sufficient human resources, especially for the management and tourism industries, causes the need for human resources in these fields to increase. SMK Negeri 2 Batam is a public school established in 2006 with "A" accreditation in the heart of Batam, Jalan Pemuda 5, Legenda Malacca. This public school has five academic programs: fashion, hospitality, tourism, fashion, and catering. This study uses the MDLC method, one of the software development methodologies according to Luther from Binanto in research. The multimedia development methodology has six stages: concept, design, material, assembly, testing, and distribution. The results of this study are media for learning creative design products in entrepreneurship.